2022
DOI: 10.3389/fimmu.2022.820058
|View full text |Cite
|
Sign up to set email alerts
|

Method Matters: Effect of Purification Technology on Neutrophil Phenotype and Function

Abstract: Neutrophils are the most abundant leukocytes in human blood and the first cells responding to infection and injury. Due to their limited ex vivo lifespan and the impossibility to cryopreserve or expand them in vitro, neutrophils need to be purified from fresh blood for immediate use in experiments. Importantly, neutrophil purification methods may artificially modify the phenotype and functional characteristics of the isolated cells. The aim of this study was to expose the effects of ‘classical’ density-gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 36 publications
0
30
1
Order By: Relevance
“…9b ). Analyzing granulocytes and monocytes, we did find that these cells appeared strongly positive for active integrin-β2; however, it is well known that this finding is an artifact of ex vivo activation of these cells after blood collection 48 . We reasoned that evaluating potential aITGB2 CAR-T cytotoxicity impacts versus myeloid cells would require in vivo studies, in the absence of this activation artifact.…”
Section: Resultsmentioning
confidence: 61%
“…9b ). Analyzing granulocytes and monocytes, we did find that these cells appeared strongly positive for active integrin-β2; however, it is well known that this finding is an artifact of ex vivo activation of these cells after blood collection 48 . We reasoned that evaluating potential aITGB2 CAR-T cytotoxicity impacts versus myeloid cells would require in vivo studies, in the absence of this activation artifact.…”
Section: Resultsmentioning
confidence: 61%
“…Human neutrophils purified by density-gradient centrifugation were used in the Ca 2+ signaling assay. For phenotypical analysis and protease release, neutrophils were purified via immunomagnetic isolation using the EasySep Direct human neutrophil isolation kit (StemCell Technologies, Cambridge, UK) according to the manufacturer’s instructions [ 42 ]. The ethical committee of University Hospital (UZ) Leuven approved experiments involving human neutrophils (project S58418).…”
Section: Methodsmentioning
confidence: 99%
“…However, the purification procedure can significantly influence the functional and phenotypical characteristics of the isolated neutrophils. Indeed, Blanter et al demonstrated the importance of choosing the correct methodology for the unbiased study of neutrophils in vitro 26 26–28 .…”
Section: Common Technical Pitfalls In the Investigation Of Neutrophil...mentioning
confidence: 99%
“…Indeed, Blanter et al demonstrated the importance of choosing the correct methodology for the unbiased study of neutrophils in vitro 26 26–28 . A high level of purity of the neutrophils is also required when performing in vitro experiments.…”
Section: Common Technical Pitfalls In the Investigation Of Neutrophil...mentioning
confidence: 99%
See 1 more Smart Citation